AN ANALYSIS OF DEIXIS USED IN FACEBOOK AND INSTAGRAM POSTED BY EFL STUDENTS - Agustina Agustin Anggraini; Urai Salam; Eka Fajar Rahmani (IKIP Siliwangi, 2024)
The aims of this study are to find out types of deixis used, the most dominant deixis and the interpretation of deixis used by EFL students. Descriptive research was used for this study. The participants of this research was 65 EFL students in English Language Department batch 2020 Univeristas Tanjungpura Pontianak. The data source was the English posts in Facebook and Instagram posted from January 2022 until December 2022. The research findings showed that 5 out of 5 types of deixis with in total 571 data used by EFL students in their Facebook and Instagram posts. The most dominant deixis used is person deixis with 363 data or 63,57%, place deixis with 97 data or 16,98%, and time deixis 65 data or 11,38%. The interpretation of person deixis as the dominant used by the EFL students to interpret the used of Instagram and Facebook to share their stories, from their point of view of how a person felt at the moment. The implication of this research helps EFL students to navigate the use of context, improving the ability to communicate affectively and understand the variations in both written and spoken English.